Foreign scientific contributions in the study of Carrion's Disease - Álvarez-Carrasco, Ricardo Iván (2023)
The current state of knowledge of Carrión's Disease, a pathology that exists mainly in some areas of the Peruvian highlands, is due, to a large extent, to the investigations of doctors of that nationality, however, doctors, other scientists, travelers, publications and technological advances from other countries have also provided contributions on this nosological entity, some transcendent and others counterproductive. The purpose of this article is to acknowledge such contributions in the context of the evolution of scientific and historical knowledge of this disease.